2020
DOI: 10.3390/ijms21176418
|View full text |Cite
|
Sign up to set email alerts
|

Immobilization of BMP-2 and VEGF within Multilayered Polydopamine-Coated Scaffolds and the Resulting Osteogenic and Angiogenic Synergy of Co-Cultured Human Mesenchymal Stem Cells and Human Endothelial Progenitor Cells

Abstract: We have previously reported the fabrication of a polycaprolactone and hydroxyapatite composite scaffold incorporating growth factors to be used for bone regeneration. Two growth factors were incorporated employing a multilayered coating based on polydopamine (PDA). In particular, Bone morphogenetic protein-2 (BMP-2) was bound onto the inner PDA layer while vascular endothelial growth factor (VEGF) was immobilized onto the outer one. Herein, the in vitro release of both growth factors is evaluated. A fastest VE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 58 publications
3
25
0
Order By: Relevance
“…Additionally, the porosity and connectivity among the pores are two important parameters. While high porosities of~80% are regarded as optimal for the regeneration of new bone, cell ingrowth is also highly dependent on the degree of connectivity among the pores [220][221][222][223][224]. Additionally, recent studies are also indicating that interconnected pores are necessary to allow for the circulation of nutrients, waste and to promote the migration of cells to the center of the implant [225,226].…”
Section: Porositymentioning
confidence: 99%
“…Additionally, the porosity and connectivity among the pores are two important parameters. While high porosities of~80% are regarded as optimal for the regeneration of new bone, cell ingrowth is also highly dependent on the degree of connectivity among the pores [220][221][222][223][224]. Additionally, recent studies are also indicating that interconnected pores are necessary to allow for the circulation of nutrients, waste and to promote the migration of cells to the center of the implant [225,226].…”
Section: Porositymentioning
confidence: 99%
“… Dashtimoghadam et al (2020) demonstrated conjugation of BMP-2 growth factor onto monodisperse polymeric microcarriers encapsulating VEGF growth factor, which displayed an additive effect on bone regeneration. Moreover, in the study of Godoy-Gallardo et al (2020) , BMP-2 was bound onto the inner polydopamine layer, whereas VEGF was immobilized onto the outer one, and the two growth factors played a synergistic effect on bone regeneration. Compared with a fast–slow VEGF growth factor delivery followed by a slow-sustained release of BMP-2 growth factor for normal bone in these two studies, we provide a favorable option that supplies BMP-2 and VEGF molecular signals in the form of peptides with greater advantage, and a burst-release followed by slow-sustained release mode of BMP-2 and VEGF peptides is better to fit the specific need of diabetic bone regeneration.…”
Section: Discussionmentioning
confidence: 99%
“…During tissue regeneration, different GF profiles are present, and the multilayer biotechnology is an open venue that allows for building GF carriers with appropriate delivery kinetics that are able to simulate those GF profiles. For instance, a polydopamine multilayered coating was used to associate BMP-2 and VEGF, where BMP-2 was bound onto the inner layer and VEGF was bound onto the outer layer [ 141 ]. The authors reported a more rapid VEGF delivery succeeded by a gentle and more continuous release of BMP-2.…”
Section: Encapsulation Incorporation and Related Delivery Stratementioning
confidence: 99%